Weighted Lin-Wang Tests for Crossing Hazards. (30th March 2014) - Koziol, James A.; Jia, Zhenyu
Abstract : Lin and Wang have introduced a quadratic version of the logrank test, appropriate for situations in which the underlying survival distributions may cross. In this note, we generalize the Lin-Wang procedure to incorporate weights and investigate the performance of Lin and Wang's test and weighted versions in various scenarios. We find that weighting does increase statistical power in certain situations; however, none of the procedures was dominant under every scenario.